2011
DOI: 10.1353/foc.2011.0017
|View full text |Cite
|
Sign up to set email alerts
|

Children with Health Issues

Abstract: All children, even the healthiest, have preventive and acute health care needs. Moreover, a growing number of children are chronically ill, with preventive, acute, and ongoing care needs that may be much more demanding than those for healthy children. Because children are unable to care for themselves, their parents are expected to provide a range of health care services without which the current health care system for children would not function. Under this “shadow health care system,” parents or parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 50 publications
1
53
0
1
Order By: Relevance
“…Need factors, including the severity and instability of the child's condition, and specific diagnoses, are important predictors of time spent providing health care for the child at home and arranging/coordinating care. These findings concur with those of previous studies that identified families of children who were severely and frequently affected by their conditions, or whose health care needs frequently changed, as experiencing the highest time burdens (Bramlett et al, 2009;DuPaul et al, 2013;Kuo et al, 2011b;McCann et al, 2012;McManus et al, 2011;Okumura et al, 2009;Schuster et al, 2011). Measures of stability and severity, based on health status questions like those on the NS-CSHCN (NCHS, 2011), could provide relatively simple ways for clinicians to screen patients for high risk of time burden.…”
Section: Implications Of Research Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Need factors, including the severity and instability of the child's condition, and specific diagnoses, are important predictors of time spent providing health care for the child at home and arranging/coordinating care. These findings concur with those of previous studies that identified families of children who were severely and frequently affected by their conditions, or whose health care needs frequently changed, as experiencing the highest time burdens (Bramlett et al, 2009;DuPaul et al, 2013;Kuo et al, 2011b;McCann et al, 2012;McManus et al, 2011;Okumura et al, 2009;Schuster et al, 2011). Measures of stability and severity, based on health status questions like those on the NS-CSHCN (NCHS, 2011), could provide relatively simple ways for clinicians to screen patients for high risk of time burden.…”
Section: Implications Of Research Findingssupporting
confidence: 88%
“…To help their chronically ill children attain optimal health, parents undertake a considerable amount of care beyond that provided by the formal healthcare sector (Schuster et al, 2011), providing health care at home themselves, and arranging/coordinating the care of formal providers. Such care places substantial demands on their time: more than half of families with CSHCN spent at least an hour/week arranging/coordinating health care, and a third spent at least an hour/week providing health care at home.…”
Section: Implications Of Research Findingsmentioning
confidence: 99%
“…Paid leave for children's health needs: a policy enabling an employee to take time off in order to care for the health needs of a child stress and anxiety (19,80,92,97,103). Parental involvement can improve recovery from both physical and mental health conditions (48,96).…”
Section: Figurementioning
confidence: 99%
“…Their care requires numerous visits to primary care doctors, specialists, and emergency rooms, and a wide array of specialized and ancillary services [16]. Such complex needs place heavy responsibility for arranging and coordinating services on families [unpublished data], who are often not well equipped for the job [18]. …”
Section: Introductionmentioning
confidence: 99%